Normal MRI features of the manica flexoria in horses and evaluation of the anatomic variability between forelimbs and hindlimbs - Samantha Miles; Charles McCauley; Mariano Carossino; Fabio Del Piero; Chin-Chi Liu; Lorrie Gaschen (PLoS ONE, 2025)
Manica flexoria tears are increasingly recognized as a cause of lameness in horses resulting in a need for improved pre-operative diagnosis. Partial tears are difficult to pre-operatively diagnose and thus research for diagnostics of manica flexoria tears has been seen in increasing frequency over the past decade, though a deficit of information exists for the features of this structure on MRI, which is best suited for evaluation of soft tissues. The goal is to perform an observational study on the morphometry of the normal manica flexoria prospectively and describe it retrospectively on MRI. Inclusion criteria includes: MRI of the metacarpophalangeal/metatarsophalangeal regions in non-lame limbs without MRI tendon abnormalities identified, and the entire manica flexoria included on transverse proton density-weighted images. The manica flexoria on MRI was measured at the proximal and distal margins, halfway between (middle), and halfway between the middle and proximal margin (proximal fourth), with measurements including dorsal, lateral/medial and dorsolateral/dorsomedial thickness. Eighteen MRI studies fit the inclusion criteria: 6 forelimbs, 12 hindlimbs. The manica flexoria on gross dissection was thicker proximally in forelimbs, and thinner proximally in hindlimbs where it blends with overlying fascia. On proton density-weighted images, the manica flexoria was hyperintense to the superficial digital flexor tendon (12/18), isointense (3/18), or hyperintense proximally and isointense distally (3/18). The proximal fourth dorsal measurements were the thickest in both forelimbs and hindlimbs on MRI images compared to other measurement sites within the same limb. The forelimb medial aspect was thicker than the lateral aspect in the proximal fourth and middle (average 17.1% thicker, p = 0.0372, 22.7% p = 0.0183, respectively), and in the hindlimb the lateral aspect was thicker in these regions (average 50.4% thicker p = 0.0099 and 23.7% p = 0.0394, respectively). This study provides an anatomical and morphometric reference for future studies evaluating abnormalities of the manica flexoria on MRI.